2001
DOI: 10.1542/peds.108.6.1263
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continuity in a Resident Versus Private Practice

Abstract: Although continuity for all visits in this RCP was less than in private practice, it was surprisingly high, considering the limited time residents spend in clinic. In a particularly important area for continuity, health maintenance visits, continuity was identical to one and superior to the other private practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 25 publications
0
52
0
1
Order By: Relevance
“…Continuity was lower on average in residency training sites compared to nonteaching community practices, which is consistent with prior literature. 25 However, we found significant variability in continuity among residency sites and found that resident practices with the highest continuity approached that of the nonteaching practices in the community. This suggests that, under the right circumstances, residency practices can achieve continuity rates comparable to those of nonteaching practices.…”
Section: Discussionmentioning
confidence: 65%
“…Continuity was lower on average in residency training sites compared to nonteaching community practices, which is consistent with prior literature. 25 However, we found significant variability in continuity among residency sites and found that resident practices with the highest continuity approached that of the nonteaching practices in the community. This suggests that, under the right circumstances, residency practices can achieve continuity rates comparable to those of nonteaching practices.…”
Section: Discussionmentioning
confidence: 65%
“…25,26 PHY is the percentage of visits in which residents see their own patients. Thus, PHY reflects continuity from the perspective of the provider and is appropriate for evaluating the educational experience of residents.…”
Section: Workload and Continuity Variablesmentioning
confidence: 99%
“…Thus, PHY reflects continuity from the perspective of the provider and is appropriate for evaluating the educational experience of residents. 25 …”
Section: Workload and Continuity Variablesmentioning
confidence: 99%
“…Continuity was measured using 2 methods: the usual provider of care method (UPC), 14,15 and the continuity for physician method (PHY). 16,17 The UPC is defined as the percentage of visits in which patients see their primary resident, whereas the PHY is defined as the percentage of visits for residents in which they see their own patients. Ambulatory workload was defined based on volume as the total number of patient visits provided by each resident during the study period divided by the number of clinics attended.…”
Section: Practice Metricsmentioning
confidence: 99%